18F-FDG PET/CT longitudinal studies in patients with advanced metastatic melanoma for response evaluation of combination treatment with vemurafenib and ipilimumab - Sachpekidis, Christos; Kopp-Schneider, Annette; Hakim-Meibodi, Lara-Elena; Dimitrakopoulou-Strauss, Antonia; Hassel, Jessica C. (Melanoma research, 2019)
Sixteen BRAF-mutation positive, metastatic melanoma patients with highly advanced disease received combination therapy of vemurafenib and ipilimumab as an individual treatment decision. Our aim was to assess the role of fluorine-18-fluorodeoxyglucose (18F-FDG) PET/computed tomography (PET/CT) in the evaluation of the clinical benefit (CB) of this combination treatment. After clinical improvement under vemurafenib monotherapy, four cycles of ipilimumab were additionally administered. 18F-FDG PET/CT was performed before the start, after two cycles and after completion of the combined ipilimumab/vemurafenib treatment. PET-based patient response evaluation to treatment was based on the European Organization for Research and Treatment of Cancer and the PET Response Evaluation Criteria for Immunotherapy criteria. Progression-free survival (PFS) from the end of combination treatment was calculated. According to their best clinical response at the end of combination treatment, eight patients showed CB and eight patients had no-CB. Two patients revealed extraordinary good clinical outcome with PFS of more than 5 years. Overall, 13 out of 16 patients were correctly classified by the European Organization for Research and Treatment of Cancer and 15 out of 16 by the PET Response Evaluation Criteria for Immunotherapy criteria. Median PFS was 8.8 months among PET-responders and 3.6 months among nonresponders. During immunotherapy administration seven patients developed radiologic signs of immune-related adverse events (irAEs), with colitis and arthritis being the most frequent ones; these patients had a significantly longer PFS than those without irAEs (P=0.036). 18F-FDG PET/CT is a valuable tool for the evaluation of patients receiving a combination of targeted treatment and immunotherapy. The appearance of irAEs on PET/CT might correlate with benefit to immunotherapy.
Im Titel ist 18 hochgestellt
Gesehen am 14.05.2019